Feminist thought and Systematic Theology - Turner, Pauline (Horizons, 1984)
Trying to answer the question, "How can a teacher of systematic theology incorporate the insights provided by feminist thinkers?", we faced several major problems and made a few rather arbitrary choices. Ultimately it is impossible to separate systematic theology from biblical or historical studies or distinguish it satisfactorily from the study of spirituality or morality. What we say here, then, must be complemented by the other essays in this series. Besides, the impact of feminist thought on Christian theology is not a peripheral or additional thing; incorporating feminist theology into systematics does not mean only an addition of topics. Rather, the research and reflection of feminist scholars demand revision of our basic approach to doing theology; they recast the basic evidence on which we must reflect; they challenge the presuppositions and methodology with which we previously approached the classic topics of theology.What we are talking about is not how to teach a special branch or brand of theology, but simply teaching systematic theology more adequately and critically, trying to lead students to understand accurately and personally what is meant by "grace" and "salvation" and "Jesus as the Christ" and "Church" and "God." In our trying to reach this goal, present-day feminist thought has proved a rich and indispensable resource—this we will try to explain in relation to four large areas of what generally is thought of as "systematic theology." Rather than sketch a course in "Systematic Theology from a Feminist Perspective," which would be both interesting and valuable, we will try to indicate ways in which the entire content of theology needs to be changed by feminist understandings.